Adobe Photoshop CS6 for photographers : a professional image editor's guide to the creative use of Photoshop for the Macintosh and PC - Evening, Martin (Burlington, Mass. : Focal Press, 2012)
Renowned photographer and Photoshop hall-of-famer, Martin Evening returns with his comprehensive guide to Photoshop. This acclaimed work covers everything from the core aspects of working in Photoshop to advanced techniques for refined workflows and professional results. Using concise advice, clear instruction and real world examples, this essential guide will give you the skills, regardless of your experience, to create professional quality results. A robust accompanying website features sample images, tutorial videos, bonus chapters and a plethora of extra resources. Quite simply, this is the essential reference for photographers of all levels using Photoshop. - Publisher.
Includes index.
Keywords: Adobe Photoshop; Photography -- Digital techniques